2021
DOI: 10.1039/d1nj00047k
|View full text |Cite
|
Sign up to set email alerts
|

The latest strategies in the fight against the COVID-19 pandemic: the role of metal and metal oxide nanoparticles

Abstract: The outbreak of the COVID-19 epidemic, which appeared at the end of 2019, has had a tremendous impact on the entire world, both in terms of health, economically, and environmentally....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 55 publications
(65 reference statements)
0
30
0
Order By: Relevance
“…They also clarify that the nanocluster can be applied to other surfaces like metals, ceramics, glasses, and polymers. Metallic oxides have also been investigated (MALLAKPOUR et al, 2021).…”
Section: Fibers Functionalizationmentioning
confidence: 99%
“…They also clarify that the nanocluster can be applied to other surfaces like metals, ceramics, glasses, and polymers. Metallic oxides have also been investigated (MALLAKPOUR et al, 2021).…”
Section: Fibers Functionalizationmentioning
confidence: 99%
“…From the beginning, scientists have examined and studied the function of the virus to can find effective ways to deal with it. They found that during the present pandemic in the absence of an efficient vaccine in place, the most available resources of respiratory protection would be infectious personal protective equipment (PPE) such as masks, various types of face coverings, respirators, and gloves [3][4][5].…”
Section: Introduction To Global Disastermentioning
confidence: 99%
“…Fig 5. Multifunctional aspects of mucoadhesive polymers preventing ocular transmission of COVID-19[20] …”
mentioning
confidence: 99%
“…In recent years, a number of different nanomaterials, such as Ag [16] , [19] , Cu [20] , [21] , Zn [22] , Ti [23] and Au [24] nanoparticles, have been developed to enhance the anti-viral and anti-bacterial properties of materials, which opens new perspectives in the prevention of COVID-19 transmission [25] . Within this context of nanomaterial development, metal–organic frameworks (MOFs) have attracted huge scientific interest as a fast-developing field of research with an increasing number of applications being proposed [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] .…”
Section: Introductionmentioning
confidence: 99%